(untitled) (Academia Journal of Medicine, 2020)
Background: The aim is to assess long term complications of type II diabetes mellitus. Subjects and Methods : One hundred twenty- six adult subjects in age range 20-60 years of either gender diagnosed with type II diabetes mellitus were selected. 5 ml of venous blood was obtained and all were subjected to fasting blood glucose, random blood glucose and glycated hemoglobin assessment. History of diet, smoking, alcoholism was obtained. Complications occurring in subjects was recorded in case history proforma. Results: Out of 126 subjects, males were 76 (60.3%) and females were 50 (39.6%). Common risk factors recorded were obesity seen in 68, alcohol in 53 and smoking in 48. The difference was non significant (P> 0.05). Common long- term complications were retinopathy seen in 72, neuropathy in 30, nephropathy in 48, hypertension in 97, diabetic foot in 56 and impotency in 32 patients. The difference was significant (P< 0.05). Conclusion: Common long- term complications were retinopathy, neuropathy, nephropathy, hypertension, diabetic foot and impotency. Background: The aim is to assess long term complications of type II diabetes mellitus. Subjects and Methods : One hundred twenty- six adult subjects in age range 20-60 years of either gender diagnosed with type II diabetes mellitus were selected. 5 ml of venous blood was obtained and all were subjected to fasting blood glucose, random blood glucose and glycated hemoglobin assessment. History of diet, smoking, alcoholism was obtained. Complications occurring in subjects was recorded in case history proforma. Results: Out of 126 subjects, males were 76 (60.3%) and females were 50 (39.6%). Common risk factors recorded were obesity seen in 68, alcohol in 53 and smoking in 48. The difference was non significant (P> 0.05). Common long- term complications were retinopathy seen in 72, neuropathy in 30, nephropathy in 48, hypertension in 97, diabetic foot in 56 and impotency in 32 patients. The difference was significant (P< 0.05). Conclusion: Common long- term complications were retinopathy, neuropathy, nephropathy, hypertension, diabetic foot and impotency. Background: The aim is to assess long term complications of type II diabetes mellitus. Subjects and Methods : One hundred twenty- six adult subjects in age range 20-60 years of either gender diagnosed with type II diabetes mellitus were selected. 5 ml of venous blood was obtained and all were subjected to fasting blood glucose, random blood glucose and glycated hemoglobin assessment. History of diet, smoking, alcoholism was obtained. Complications occurring in subjects was recorded in case history proforma. Results: Out of 126 subjects, males were 76 (60.3%) and females were 50 (39.6%). Common risk factors recorded were obesity seen in 68, alcohol in 53 and smoking in 48. The difference was non significant (P> 0.05). Common long- term complications were retinopathy seen in 72, neuropathy in 30, nephropathy in 48, hypertension in 97, diabetic foot in 56 and impotency in 32 patients. The difference was significant (P< 0.05). Conclusion: Common long- term complications were retinopathy, neuropathy, nephropathy, hypertension, diabetic foot and impotency. Background: The aim is to assess long term complications of type II diabetes mellitus. Subjects and Methods : One hundred twenty- six adult subjects in age range 20-60 years of either gender diagnosed with type II diabetes mellitus were selected. 5 ml of venous blood was obtained and all were subjected to fasting blood glucose, random blood glucose and glycated hemoglobin assessment. History of diet, smoking, alcoholism was obtained. Complications occurring in subjects was recorded in case history proforma. Results: Out of 126 subjects, males were 76 (60.3%) and females were 50 (39.6%). Common risk factors recorded were obesity seen in 68, alcohol in 53 and smoking in 48. The difference was non significant (P> 0.05). Common long- term complications were retinopathy seen in 72, neuropathy in 30, nephropathy in 48, hypertension in 97, diabetic foot in 56 and impotency in 32 patients. The difference was significant (P< 0.05). Conclusion: Common long- term complications were retinopathy, neuropathy, nephropathy, hypertension, diabetic foot and impotency. Background: The aim is to assess long term complications of type II diabetes mellitus. Subjects and Methods : One hundred twenty- six adult subjects in age range 20-60 years of either gender diagnosed with type II diabetes mellitus were selected. 5 ml of venous blood was obtained and all were subjected to fasting blood glucose, random blood glucose and glycated hemoglobin assessment. History of diet, smoking, alcoholism was obtained. Complications occurring in subjects was recorded in case history proforma. Results: Out of 126 subjects, males were 76 (60.3%) and females were 50 (39.6%). Common risk factors recorded were obesity seen in 68, alcohol in 53 and smoking in 48. The difference was non significant (P> 0.05). Common long- term complications were retinopathy seen in 72, neuropathy in 30, nephropathy in 48, hypertension in 97, diabetic foot in 56 and impotency in 32 patients. The difference was significant (P< 0.05). Conclusion: Common long- term complications were retinopathy, neuropathy, nephropathy, hypertension, diabetic foot and impotency.